Impact of COVID-19 on University Education, Nepal - K.C., Tulza (Tribhuvan University Journal, 2020)
The corona virus disease 2019 (COVID-19) has now become a pandemic and major health threat. Almost countries of the world including Nepal have suspended their academic activities by closing schools and colleges. Some attempts are being made to overcome this gap by providing virtual classes to the students. But such efforts are also being proven inaccessible and challenging especially for the poor students residing in remote parts of the countries. Regarding the practical courses where acquisition of psychomotor skill by the students is mandatory together with other cognitive and affective skill, virtual online classes remain ineffective. The date and time of opening of schools and colleges has become unpredictable. In this review, the author has highlighted the potential impacts of this outbreak in education, academic institutions, and students.